Train Control Method for Through Operation of Inter-city Railway and Urban Rail Transit - JIANG Hongkuo (Kongzhi Yu Xinxi Jishu)
There are many differences between the inter-city railway train control system (CTCS) and the urban rail transit train control system (CBTC) . However, the demand for continuous operation of inter-city railways and urban rail transit lines is increasingly urgent. To this end, this paper analyzes the architectures and train control principles of CBTC and CTCS train control systems, and compares and sorts out the differences and commonalities between the two systems from the aspects of train control patterns and function, etc. Based on the research, a compatible train control scheme is proposed together with an in-depth analysis of the core technologies involved in the scheme, such as layout of ground signal equipment and design of vehicle-level signal equipment configuration-level control logic. Finally, it takes a typical scenario as an example to demonstrate the train control process that a train enters an urban rail line from an inter-city line. The results show that the compatible train control scheme can meet the needs of the existing inter-city railways and urban rail lines for continuous operation, and can also be used for related services.